Determinants of Capital Structure Analysis: Empirical Study of Telecommunication Industry in Indonesia 2008-2015 - Rahmatillah, Intan; Prasetyo, Ahmad Danu (Journal of Business and Management, 2016)
Abstract.The capital structure is an essential element in the firmâ€™s long-term financial strategic decision. Generally, the firmâ€™s management tends to create leverage with the optimal capital structure as the target. The optimal capital structure reflects proportional number of debt and equity to maximize the return on investment and firmâ€™s value alongside minimizes the cost of capital that directly protects the firm from any potential risks such as bankruptcy and financial distress.Many studies have been discovered the contemporary capital structure theory which helps the firms to understand financing behavior with the capital structure determinants. But, these theories also proposed different hypotheses/assumptions regarding the capital structure. The result of those studies does not lead to a concurrence for the specific factors that affect the capital structure so that the theories cannot perfectly explain the ideal financing decisions. Therefore, this research focuses on investigating the capital structure regarding the MoF (Minister of Finance) regulation No. 169/PMK.010/2015, the government limits the Debt to Equity Ratio (â€œDERâ€) maximum of 4:1 which effective for Fiscal Year 2016. One of the industries that will be restructured their capital is telecommunication. They had an important role as one of the key industries in Indonesia. This final project reviews the capital structure theories to formulate testable hypotheses regarding the determinants of capital structure. The panel data econometric techniques are used to investigate the most significant factors that affect the capital structure of telecommunication industry in Indonesia which represented by five listed telecom firms with the largest market capitalization in Indonesia Stock Exchange (IDX) during 2008-2015. The final project processes the data from secondary sources to be tested in a statistical software STATA.11. The result shows 68.5% variation of the dependent variables (leverage/TDR) of capital structure as a whole can be explained by the variables in the model such as profitability, size, tangibility, liquidity, risk, the effective tax rate, ownership, interest rate and GDP, while the remaining 31.5% is influenced by other variables outside the system. The final project suggests the most significant factors that affect the capital structure such as size, tangibility, liquidity, risk, interest rate, GDP and ownership which consistent with some capital structure theories. It is suggested for managers in the telecommunication industry in Indonesia to consider those factors when restructuring their capitals or others financial decision. However, the optimal capital structure variable evidently does not affect the firmâ€™s value in industry level. The result indicates that firm value independent of the capital structure due to behavioral factors of the investors in Indonesia who tend to ignore the fundamental factor(s) of the firm.Keywords: Indonesiaâ€™s telecommunication industry, capital structure, leverage, value of the firm